2022
DOI: 10.53575/irjmss.v3.2.14(22)153-162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Relationship of School Collegiality and Professional Development of Senior Secondary School Teachers of Khyber Pakhtunkhwa

Abstract: Education is the major channel of sharing and cooperation among all faculty members working inside an institute. Strong bonds of teamwork and active collaboration provide smooth and vital pathways for attainment of desired aims. Collegiality refers to professional relationship at workplaces. This relationship is considered vital for the professional development of colleagues in any field of life especially in the field of education. This study intends to explore the collegiality among senior secondary school t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…However, the problem in Pakistan remains under-researched, particularly in Sindh, where the educational landscape has diverse challenges. The study by Zaman, Sajjad, and Gharsheen (2023) suggests that the issue is pertinent to the region. However, a comprehensive understanding of the problems encountered by urban school set-up teachers and students in Sindh is yet to be developed.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…However, the problem in Pakistan remains under-researched, particularly in Sindh, where the educational landscape has diverse challenges. The study by Zaman, Sajjad, and Gharsheen (2023) suggests that the issue is pertinent to the region. However, a comprehensive understanding of the problems encountered by urban school set-up teachers and students in Sindh is yet to be developed.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…A questionnaire was used to collect data from the study; data collected were analyzed using frequency counts and percentages. Consequently, it was found that there was a high level of attitude among students based on the influence of teacher performance (Ahmad et al, 2013).…”
Section: Significance On the Relationship Between Teacher Performance...mentioning
confidence: 99%
“…It was advised that education administrators were supposed to take the teacher qualifications into account when recruiting and placing national senior secondary teachers. Other researchers like, Ahmad, Shaheen & Hussain (2022) analyzed the current teacher recruitment policy decisions in Khyber Pakhtunkhwa Province to replace pre-service professional qualifications. Their study found that the current teacher recruitment policy was not in line with any previous national education policy in Pakistan, nor was it in line with the National Education Policy 2017.…”
Section: Total Quality Management (Tqm)mentioning
confidence: 99%